Pengaruh Niat, Sikap, dan Norma Subjektif terhadap Minat Penggunaan Aplikasi Sistem Informasi Manajemen Aset Negara (SIMAN) Versi 2 di Kantor Pelayanan Kekayaan Negara dan Lelang Surabaya - Nur Laily Zumrotul Khasana; Eva Hany Fanida; Meirinawati Meirinawati; Trenda Aktiva Oktariyanda (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Digital transformation in the management of state property is a necessary step towards achieving transparent and accountable governance. The Minstry of Finance, through the Directorate General of State Assets, has developed the State Asset Management Information System Version 2 application as a means of digital based management, but its implementation still faces challenges related to interest in its use by work unit operators. This study aims to evaluate the impact of intentions, attitudes, and subjective norms on interest in using the SIMAN V2 application at the Surabaya State Assets and Auction Service Office using the Theory of Reasoned Action (TRA) approach. Using a quantitative design through a survey, this study was conducted at the Surabaya KPKNL with subjects being SIMAN V2 application operators in work units in the working area. Data colection techniques used a questionnaire with a Likert scale. Data analysis was performed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) using SmartPLS software. The results of the study indicate that intention, attitude, and subjective norms have a positive and significant effect on interest in using the SIMAN V2 application. This study shows that psychological and social factors play an important role in supporting technology adoption in the public sector. The conclusion emphasizes that increased interest in use can be achieved by strengthening individual intentions, forming positive attitudes, and providing workplace support. Increased socialization, ongoing technical training, and recommendations for further research institutional supportfrom agencies to optimize the use of the SIMAN V2 application.